Programming 101 The How and Why of Programming Revealed Using the Processing Programming Language - Meyer, Jeanine (Apress, 2018)
Understand the importance of programming, even if you've never programmed before! This book will teach you the basics of programming using the Processing programming language. You will create your own Processing sketches, using personal images, themes, or hobbies that you enjoy. The chapters in the book will demonstrate the process of programming, starting with formulating an idea, planning, building on past projects, and refining the work, similar to writing an essay or composing a song. This approach will guide you to make use of logic and mathematics to produce beautiful effects. The term for program in Processing is sketch, though the sketches featured in this book are far more than static drawings; they incorporate interaction, animation, video, audio, and accessing files on the local computer and on the Web. Technical features are introduced and explained in the context of complete examples: games (Snake, Hangman, jigsaw, slingshot), making a collage of family images and video clips, preparing directions for folding an origami model, rotating objects in 3D, and others. Programming is a fun, creative, expressive pursuit. It requires attention to details and can be frustrating, but there is very little that compares to the satisfaction of building a program out of nothing and making it work (or taking an existing program and fixing a problem, or adding a feature and making it better). Programming 101 is your gateway to making this happen.